Novel Mucoadhesive Film Forming Spray Systems: Mechanism, Formulation Approaches and Therapeutic Perspectives - Damane Madhuri; Sameer Shafi; Waghmare Pranita; Gadhave Ankita; Swami Shivlila (Asian Journal of Pharmaceutical Research and Development, 2026)
Mucoadhesive film-forming sprays (FFS) have emerged as advanced and promising drug delivery systems for mucosal administration owing to their ability to prolong residence time, improve drug absorption, and provide sustained therapeutic action. Conventional dosage forms such as tablets, creams, gels, and ointments often suffer from limitations including poor retention, variable absorption, frequent dosing, and reduced patient compliance. In contrast, mucoadhesive film-forming sprays combine the advantages of mucoadhesive polymers and in situ film formation to enhance localized and systemic drug delivery through buccal, nasal, and vaginal mucosal routes. These systems transform from liquid formulations into thin adhesive polymeric films following solvent evaporation, thereby ensuring uniform drug distribution, improved adhesion, flexibility, and prolonged drug release.The present review discusses the anatomy and physiology of mucosal membranes with particular emphasis on buccal, nasal, and vaginal mucosa, including their permeability, vascularization, mucus composition, and suitability for drug delivery. Various theories and mechanisms of mucoadhesion are also described. Additionally, the formulation aspects of film-forming sprays, including polymers, solvents, plasticizers, penetration enhancers, bioadhesive agents, and preservatives, are comprehensively reviewed. Important physicochemical evaluation parameters such as pH, viscosity, spray angle, mucoadhesive strength, washability, permeability studies, and stability studies are highlighted.Furthermore, the therapeutic applications of mucoadhesive film-forming sprays are discussed. Due to their non-invasive nature, improved patient compliance, and enhanced bioavailability, mucoadhesive film-forming sprays represent a novel and effective platform for mucosal drug delivery and hold significant potential for future pharmaceutical and clinical applications.